Shear bond strength of different lingual buttons bonded to wet and dry enamel surfaces with resin modified glass ionomer cement (in vitro comparative study) - Hiba M Alkhateeb; Eman I Al-Sheakli (College of Dentistry/ University of Baghdad, 2014)
Background: This study was aimed to investigate the effect of three lingual button (Nickel free / rectangular base, Nickel free / round base and Composite) and bonding environment, wet and dry enamel surface, on: the shear bond strength (SBS) of light and self-cured Resin Modified Glass Ionomer Cements, and the debonding failure sites. Materials and method: One hundred twenty no-carious, free of cracks maxillary first premolar teeth were selected. Three types of orthodontic lingual buttons were used in this study: Nickel free / rectangular base, Nickel free / round base and Composite buttons. The teeth were divided into two groups of sixty teeth each. One group was used for testing the chemically cured GC Fuji Ortho Resin modified Glass Ionomer (RMGIC), while the other was used for testing the light cured GC Fuji Ortho LC RMGIC. Each was further subdivided into two subgroup; thirty teeth were bonded to wet enamel surface while the other was bonded after drying the enamel surface. Then each ten teeth from each subgroup were bonded with only one type of buttons. The sample was tested for bond strength using the universal testing machine and the Adhesive Remnant Index (ARI) was inspected under the stereomicroscope. Results:The highest (SBS) values were obtained in the Nickel free / round base button with both types of RMGIC in wet and dry environment as revealed by ANOVA test. While t-test revealed that both systems of RMGIC yield relatively lower values of (SBS). Conclusions:The GC Fuji Ortho RMGICs resist shear force in dry better that in wet environment.Nickel free / round base buttons give the greatest shear bond strength among the three types of button.The composite buttons give greater bond strength in dry than in wet environment with both GC Fuji Ortho and GC Fuji Ortho LC RMGICs.